The Practice of Experimental Physics - Recollections, Reflections, and Interpretations - Perl, Martin L.; Meyer, Mary A. (Theoria et Historia Scientiarum, 2007)
This article is based on Martin L. Perl’s Nobel Prix 1995 paper, “Reflections on the Discovery of the Tau Lepton,” and is supplemented by excerpts from his presentation, “Reflections on Experimental Science,” to an audience of mainly young scientists at Los Alamos National Laboratory on June 29, 1999. In both documents, Perl reflects on almost 50 years of experience in experimental science to pass on what he has learned, particularly to young people who are beginning scientific research.